2016
DOI: 10.17140/semoj-1-127
|View full text |Cite
|
Sign up to set email alerts
|

The Interventional Use of Water Treadmill Running During Long Periods of Injury

Abstract: Brief ReportPage 174 ABSTRACTThe aim of this brief study was to establish the efficacy of waist depth water Aquatic treadmill (ATM) running during a 28-day injury period where normal land based training was not possible. Synchronized tri-axial accelerometers were used to identify running dynamics while expired air and heart rate were sampled on a breath-by-breath basis for physiological variable collection throughout a 15-minute sub-maximal constant speed trial performed pre-injury, 28-days following initial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Healthy adults can tolerate long-term consumption of 2 g dietary protein per kg BW per day 32 or even a higher amount. [94][95][96][97] For example, consumption of 3 g dietary protein per kg BW per day (the highest amount tested in the study) for 3 weeks (duration of the study) did not cause any side effects in elite cyclists. 94 Macdermid et al 95 reported that cyclists could well tolerate 3.3 g dietary protein per kg BW per day (the highest amount tested in the study) for 7 days (duration of the study).…”
Section: Safe Upper Limits Of Dietary Protein Intake By Adultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Healthy adults can tolerate long-term consumption of 2 g dietary protein per kg BW per day 32 or even a higher amount. [94][95][96][97] For example, consumption of 3 g dietary protein per kg BW per day (the highest amount tested in the study) for 3 weeks (duration of the study) did not cause any side effects in elite cyclists. 94 Macdermid et al 95 reported that cyclists could well tolerate 3.3 g dietary protein per kg BW per day (the highest amount tested in the study) for 7 days (duration of the study).…”
Section: Safe Upper Limits Of Dietary Protein Intake By Adultsmentioning
confidence: 90%
“…[94][95][96][97] For example, consumption of 3 g dietary protein per kg BW per day (the highest amount tested in the study) for 3 weeks (duration of the study) did not cause any side effects in elite cyclists. 94 Macdermid et al 95 reported that cyclists could well tolerate 3.3 g dietary protein per kg BW per day (the highest amount tested in the study) for 7 days (duration of the study). Furthermore, based on the capacity of urea synthesis, Bilsborough and Mann 96 estimated that healthy adults can tolerate a dietary intake of 3.5 g protein per kg BW per day without side effects.…”
Section: Safe Upper Limits Of Dietary Protein Intake By Adultsmentioning
confidence: 90%